Pemilihan Rancangan Roda Gigi Berdasarkan Karakteristik Material dengan Metode Electre - Taufiq Rochman (Performa: Media Ilmiah Teknik Industri, 2017)
Gears is one of machine elements, cylindrical wheels used for transmitting motion and power from one rotary shaft to anothers. The design of the gear is part of the engineering design activities to produce products that are not only superior in terms of technology but produce the design in accordance with the designer. The design of gear involves extensive procedure, complex calculations and many design decision. It is necessary for the design of the gear based on characteristics of material that matches the designer whishes. The characteristics of material on which to base the design include the size of the geometry, the contact stress, bending stress, precision standard and transmission conditions. Selection of gear design to consider the characteristic materials through multi criteria decision making approach. The ELECTRE method is one of MCDM method used to help decision makers choose the best alternative with outranking approach. The results of the analysis with the model ELECTRE is best alternative consists of alternative 3 that has some design criteria includes: contact stress, , bending stress, precision based on the ISO 1328 standard, transmission conditions and the size of the geometry. According to these calcultion , the absolute dominance grading was determined as alternative 3 > alternative 1 > alternative 4 >alternative 2.